2018
DOI: 10.1007/s11916-018-0664-x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ketamine Infusion in the Treatment of Complex Regional Pain Syndrome: a Systemic Review and Meta-analysis

Abstract: A search of Embase, Pubmed, Web of Knowledge, Cochrane, Clinical Trial.gov , and FDA.gov between Jan 1, 1950, and August 1, 2017, was conducted to evaluate ketamine infusion therapy in the treatment of CRPS. We selected randomized clinical trials or cohort studies for meta-analyses. I index estimates were calculated to test for variability and heterogeneity across the included studies. The primary outcome is pain relief. The effect of ketamine treatment for complex regional pain syndrome was assessed by 0-10 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 21 publications
1
42
1
3
Order By: Relevance
“…The following conclusions may be drawn from the seven systematic reviews and meta-analyses that were published since 2012 [11,[34][35][36][37][38][39]: irrespective of underlying disease, intravenous administration of ketamine seems to have the highest analgesic efficacy compared to other administration forms; the efficacy of intravenous ketamine is often rather small and does not last longer than 1-2 days following end of administration; longer administration times are associated with longer effect durations; none of the studies phenotyped their patients or restricted treatment to patients with central sensitization; most studies were effectively not blinded due to the occurrence of ketamine adverse effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The following conclusions may be drawn from the seven systematic reviews and meta-analyses that were published since 2012 [11,[34][35][36][37][38][39]: irrespective of underlying disease, intravenous administration of ketamine seems to have the highest analgesic efficacy compared to other administration forms; the efficacy of intravenous ketamine is often rather small and does not last longer than 1-2 days following end of administration; longer administration times are associated with longer effect durations; none of the studies phenotyped their patients or restricted treatment to patients with central sensitization; most studies were effectively not blinded due to the occurrence of ketamine adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…We retrieved seven relevant meta-analyses, systematic or literature reviews (Table 2). Five reviews focus on chronic neuropathic pain [11,[34][35][36][37], of which two predominantly on complex regional pain syndrome (CRPS) patients [35,37], and two reviews on cancer pain [38,39]. Although there is some overlap in studies included in the various reviews, the approach of the different reviews is sufficiently distinguishing to be included in our analysis.…”
Section: Systematic Reviews and Randomized Trialsmentioning
confidence: 99%
“…e utility of ketamine has been validated in neuropathic pain [87], especially in complex regional pain syndrome (CRPS). CRPS causes significant morbidity, and 80% of patients with CRPS are severely disabled [88]. Many patients with CRPS are unresponsive to traditional therapeutic approaches, and ketamine has been shown to reduce pain levels in some of these treatment-refractory patients [89].…”
Section: Chronic Painmentioning
confidence: 99%
“…Furthermore, both sensitization and tolerance are possible consequences of repeated ketamine use, and while the duration required to notice these effects from intermittent ketamine use has not been extensively studied in humans, in mouse studies sensitization has been shown to occur over the course of weeks and is clearly evident by 5 weeks of weekly administration of intraperitoneal ketamine (20 mg/kg or 50 mg/kg, in mice) [117]. Ketamine also has been known to cause hepatic toxicity due to mitochondrial impairment, urological toxicity including ulcerative cystitis, and immediate risks including tachyarrhythmias, hallucinations, and flashbacks [88,118,119]. Psychedelic effects are also associated with ketamine [59], and benzodiazepine coadministration may be required to treat its psychosis-like effects [58].…”
Section: Drawbacksmentioning
confidence: 99%
“…A search of PubMed on February 23, 2018, using the terms “ketamine” AND “chronic pain” and the filter “systematic reviews” yielded 20 hits, of which 4 were systematic reviews on ketamine for chronic noncancer pain in adults 6 , 19 , 32 , 61 (Table 5 ).…”
Section: Ketamine For Chronic Noncancer Painmentioning
confidence: 99%